The Rock Art of Oman 1975 - Clarke, Christopher (The Journal of Oman Studies, 1975)
Since: Bertram Thomas published the fast reports of rock art sites in Oman, in 'Alarms and Excursions in Arabia', archaeologists, geologists and geographers have added to the list as a by-product of their own activities. In an initial attempt to bring these reports together, a survey by Mr. Rudi Jäckli and myself in 1973, and further extensive discoveries by him and others in 1974, showed rock drawings to occur widely along the Oman mountains, from Runs al Jibal in the north-west, to the Sharqiya in the south-cast. Mr. Jäckli also pointed out that the clustering of the sites, which had otherwise appeared an accident of the pattern of discovery, did in fact conform closely to the formations of Cretaceous limestone, which is particularly suitable for the 'pecking' technique used for most of the drawings. The smooth limestone walls of wadis are the usual location, sometimes main wadis of passage, and sometimes blind wadis providing only very local pathways. Drawings are found also on the boulder beds of wadis, and on outcrops of limestone exotics. Carvings have been found on the stone slabs of prehistoric graves, as at Hili-9.